Job Loss, Unemployment Insurance, and Health: Evidence from Brazil - Guilherme Amorim; Diogo Britto; Alexandre Fonseca; Breno Sampaio (Institute of Labor Economics (IZA), 2024)
We study the effects of job loss and unemployment insurance (UI) on health among Brazilian workers. We construct a novel dataset linking individual-level administrative records on employment, hospital discharges, and mortality for a 17-year period, rarely available in the context of developing countries. Leveraging mass layoffs for identification, we find that job loss increases hospitalization (+33%) and mortality risks (+23%) for male workers, while women are not affected. These effects are pervasive over the distribution of age, tenure, income and education, and men's children are also negatively affected. Remarkably, about half of these impacts are driven by external causes associated with accidents and the violent Brazilian context. Using a regression discontinuity design, we show that access to UI partially mitigates the adverse effects of job loss on health. Our results indicate that the health costs of job loss are only partially explained by the income losses associated with job displacement.
Keywords: I12; J63; J65; 330; job loss; unemployment insurance; hospitalization; deaths